PERLINDUNGAN HUKUM BAGI INVESTOR TERKAIT INVESTASI ROBOT TRADING (Studi Kasus Putusan Nomor : 431/Pdt.G/2022/PN.Jkt.Brt) - Farhan Ramadhan (2023)
This research was conducted to provide implementation of Law Number 21 of 2011 concerning the Financial Services Authority regarding legal protection for investors regarding trading robot investments, to find out the legal rules that should be regarding robot trading investment activities based on Decision Number: 431/Pdt.G/2022 /PN. Jkt. Brt. The author uses this type of research, namely normative juridical. The results of this study indicate that PT. DNA Pro Academy and PT. Digital Net Assets do not have a permit from the OJK, this has been regulated in Article 4 of Law Number 21 of 2011 concerning the OJK Financial Services Authority Jo. Financial Services Authority Regulation Number 77/POJK.01/Year 2016 Concerning Information Technology-Based Money Lending Services. PT. DNA Pro Academy and PT. Digital Net Assets has clearly proven that its activities use a tiered marketing scheme system, a ponzi scheme and are not registered by BAPPEBTI, this is prohibited in Law Number 7 of 2014 concerning Trade Jo. Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing Jo. Law Number 10 of 2011 concerning Amendments to Law Number 32 of 1997 concerning Commodity Futures Trading. Besides that, OJK, BAPPEBTI and related government agencies must tighten supervision over trading robot investment activities